Biomarker responses in zebrafish (Danio rerio) following long-term exposure to microplastic-associated chlorpyrifos and benzo(k)fluoranthene - Hanslik, Lisa; Seiwert, Bettina; Huppertsberg, Sven; Knepper, Thomas P.; Reemtsma, Thorsten; Braunbeck, Thomas (Aquatic toxicology, 2022)
Continuously increasing plastic production causes a constant accumulation of microplastic particles (MPs) in the aquatic environment, especially in industrialized and urbanized areas with elevated wastewater discharges. This coincides with the release of persistent organic pollutants (polycyclic aromatic hydrocarbons (PAHs), pesticides) entering limnic ecosystems. Although the assessment of potential effects of environmental pollutants sorbed to MPs under chronic exposure scenarios seems vital, data on potential hazards and risk by combined exposure to pollutants and microplastics for aquatic vertebrates is still limited. Therefore, zebrafish (Danio rerio) were exposed over 21 days to the organophosphate insecticide chlorpyrifos (CPF; 10 and 100 ng/L) and the PAH benzo(k)fluoranthene (BkF; 0.78 and 50 µg/L) either dissolved directly in water or sorbed to different MPs (irregular polystyrene, spherical polymethyl methacrylate; ≤ 100 µm), where CPF was sorbed to polystyrene MPs and BkF was sorbed to polymethyl methacrylate MPs. Contaminant sorption to MPs and leaching were documented using GC-EI-MS; potential accumulation was studied in cryosections of the gastrointestinal tract. Enzymatic biomarkers and biotransformation were measured in liver and brain. Overall, exposure to non-contaminated MPs did not induce any adverse effects. Results of fluorescence tracking, CYP1A modulation by BkF as well as changes in acetylcholinesterase activity (AChE) by CPF were less pronounced when contaminants were sorbed to MPs, indicating reduced bioavailability of pollutants. Overall, following exposure to waterborne BkF, only minor amounts of parent BkF and biotransformation products were detected in zebrafish liver. Even high loads of MPs and sorbed contaminants did not induce adverse effects in zebrafish; thus, the potential threat of MPs as vectors for contaminant transfer in limnic ecosystems can be considered limited.